Karakteristik Lignin Empat Jenis Bambu (Lignin Characteristic of Four Bamboo Species) - Deded S Nawawi; Rita K Sari; Nyoman J Wistara; Adesna Fatrawana; Puji Astuti; Wasrin Syafii (Jurnal Ilmu dan Teknologi Kayu Tropis, 2019)
Lignin is one of the major component of bamboo, together with cellulose and hemicellulose, which may differ comparing to wood lignin. Lignin characteristics of four bamboos species, i.e.  betung (Dendrocalamus asper), ampel (Bambusa vulgaris), andong (Gigantochloa nigrociliata), and tali (Gigantochloa apus) were investigated. As lignin characteristics;  lignin content and proportion of lignin monomer were investigated by Klason method, UV spectrophotometry, and Pyrolysis Gas-Chromatography analysis, respectively. Lignin content of bamboos varies depending on species and position of sample. Bamboo lignin was categorized into syringyl-guaiacil-p-hydroxyohenil (S-G-H) lignin. There was high correlation between proportion of syringyl unit with acid-soluble lignin obtained during Klason lignin procedure.